Impact of Song Dubbing on Characterization: Frozen in Persian - Khoshsaligheh, Masood; Sarvghadi, Fatemeh; Mohammad Alizadeh, Binazir (Journal of Audiovisual Translation, 2022)
Interventions in the extent and quality of the portrayal of characters in dubbed musical films can induce a change in the original characterization in the film as characters play the role of singers who reflect their inner emotions and thoughts through diegetic songs. To examine the impact of dubbed diegetic songs on the singer’s characterization, the study contains two main phases, theoretical and empirical. Initially, the development of the notions on characterization in dubbed films is illustrated to justify and present a merged model drawing on Bosseaux (2015) and Reus (2020) from the realm of Translation Studies, and the cinematic standpoints inspired by Dyer (1998). Then, to apply the model, the different dimensions of the merged model, including the visual dimension (synchrony and visual deixis) and the verbal dimension (sense, style, and voice quality) are investigated in a case of private sector, professional Persian dubbing (Khoshsaligheh, 2022). The case study was the Persian dubbed version of the diegetic songs of Frozen (Buck & Lee, 2013). The analysis reveals that the shifts in two dimensions lead to a fairly dissimilar presentation of the singers’ characterization. Lay Summary In musical films, songs by the characters are interwoven into the story. When characters sing, they reveal their inner emotions and thoughts using the song’s message. Any manipulation in dubbing of these songs into other languages can and does result in changes in how the original singers’ characterization is represented for the new audience. To study the impact of the dubbed songs on the singer’s characterization, we reviewed the previous studies and came up with a new way for characterization analysis in dubbed songs by merging and adapting some the models from translation studies and film studies fields. Next, we sued the model to study the Persian dubbed version of the songs of the hit musical animated film, Frozen (2013). The results reveal various changes in the dubbed version in terms of characterization through changing the visual and verbal aspects of the songs in a way that the Persian dubbed version portrays the singers’ characterization considerably dissimilarly.